TOLERANSI DAN BATASAN KOMUNIKASI ANTAR UMAT BERAGAMA - Ari Yunaldi (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2019)
This research uses library research (Research Library). The research method used is qualitative data analysis, the data comes from primary legal materials, secondary legal materials, and tertiary legal materials that are related to this research. The approach used in this research is to use the approach of the Ayat Al-Qur'an, Asbabul Nuzul, Juridical, and normative. The results obtained in this study are first, the existence of the concept of tolerance for Muslims and non-Muslims, read QS At-Taubah: 30 - 31. Here, we will limit the discussion on tolerance between religious communities (Muslims to non-Muslims) from the perspective of the Qur'an. 'an. Indonesia, as we all know, is a country that gives freedom to each individual, everyone has the same right to embrace religion. Namely, the 1945 Constitution, Article 29 paragraph 2: The state guarantees the freedom of everyone to embrace their respective religions and to worship according to their religion and belief. Article 29 paragraph (2) of the 1945 Constitution states that the State guarantees the independence of every citizen to embrace religion. Second, Verses About Tolerance and Inter-Religious Communication, Surah Al-Khafirun verses 1-6 and Surah Mumthahanah verses 8-9. Third, the boundaries of communication between religious communities. To avoid the potential for the disintegration of the nation, it is necessary to have ethics or boundaries to regulate communication between religious followers in order to realize harmony and peace between religious communities. In the rules of Ushul Fiqih, it is explained that: "Rejecting the damages takes precedence over attracting the benefits (otherwise it is very possible that the afraid is obtained, while the mashallah not produced)."